The problem of speaking for others - Alcoff, Linda (Cultural Critique, 1991)
Keywords: approches et analyses; cours; discipline; discours dominant; fem3400; phi4336; pol4212; premier cycle; privilèges; ressource en ligne; sciences humaines; systèmes d'oppressions; épistémologie

Imagined communities: Reflections on the origin and spread of nationalism - Anderson, Benedict (Verso, 1991)
L'ouvrage mondialement connu sur les origines et le développement du nationalisme Toute l'ampleur de la réussite intellectuelle de Benedict Anderson est toujours appréciée et débattue. "Imagined Communities" reste le livre le plus influent sur les origines du nationalisme, comblant le vide qui existait auparavant dans les traditions de la pensée occidentale. Cité plus souvent que tout autre ouvrage de langue anglaise en sciences humaines, il est lu dans le monde entier dans plus de trente traductions. Rédigée avec une clarté exemplaire, cette étude éclairante retrace l'émergence de l'idée de communauté en Amérique du Sud, plutôt qu'en Europe au XIXe siècle. Plus tard, ce sentiment d'appartenance s'est formé et reformulé à tous les niveaux, de la haute politique à la culture populaire, en passant par l'imprimé, la littérature, les cartes et les musées. Suite à la montée et au conflit des nations et au déclin des empires, Anderson s'appuie sur des exemples de l'Asie du Sud-Est, de l'Amérique latine et du passé récent de l'Europe pour montrer comment le nationalisme a façonné le monde moderne.
Keywords: approches et analyses; colonialisme; communication; cours; discipline; discours dominant; fem1000; histoire; histoire et politique; identités culturelles; modernité; mémoire collective; mémoire culturelle; nationalisme; occident; politique; premier cycle; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty–and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Papers of the "Forth Hill Conference on Southern Culture", held at Clemson Univ. (1989). Textes de Fort Hill Conference on Southern Culture, tenue à Clemson University au printemps de 1989.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Sisters in the struggle - Brand, Dionne; Stikeman, Ginny (1991)
Ce documentaire présente des femmes noires actives en politique ainsi que dans l'organisation communautaire, syndicale et féministe. Ils partagent leurs idées et leurs témoignages personnels sur le double héritage du racisme et du sexisme, liant leurs luttes personnelles à la bataille en cours pour mettre fin à la discrimination systémique et à la violence contre les femmes et les personnes de couleur.
Keywords: amériques; approches et analyses; canada; cours; fem3300; militance; premier cycle; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

L'interloquée ; Les oubliées de l'oubli ; [et] Dé/générée - Causse, Michèle (Trois, 1991)
« L’androlecte est en effet un soliloque. C’est la production mentale, disons la pathologie langagière, de l’Andros qui, victime d’une faille principielle, n’a pas su, pas pu, pas voulu accéder au chiffre deux et qui, s’étant érigé en seul locuteur, n’a pas eu d’autre interlocuteur que lui-même. Avant même de parler, une femme en "Androlecte est inter-loquée". Soit au sens propre "interdite-interrompue". Le dictionnaire – depôt sacré des mots de l’androlecte – ne donne-t-il pas comme exemple cette phrase, ô combien illuminante: "Faute d’interlocuteur, elle se parlait à elle-même". (Petit Robert, Léon Bloy). Bécassine ayant cru sans doute dans le langage comme communication. » p.15 éditions Trois, 1990
Keywords: approches et analyses; arts; discipline; hétérosexisme; lesbianisme; sexisme; systèmes d'oppressions; études littéraires

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Mais à quoi sert une épistémologie des rapports sociaux de sexe? - Combes, Danièle (Sexe et genre. De la hierarchie entre les sexes, 1991)
S’inscrivant dans le mouvement des études féministes qui ont marqué les années quatre-vingt, cet ouvrage réunit les différents points de vue de femmes universitaires engagées dans des champs de recherches aussi divers que la biologie, le droit, la linguistique. Partant de l’examen critique de la distinction sexe et genre, elles analysent les mécanismes qui assurent le maintien de la domination masculine et font progresser la réflexion sur les déterminants de la subordination des femmes.
Keywords: 1900-1999; 1980-1989; approches et analyses; classe sociale; cours; discipline; europe; fem1000; france; histoire et politique; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; épistémologie

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Daughters of the dust - Dash, Julie (Cohen Film Collection, 1991)
At the dawn of the 20th century, a multi-generational family in the Gullah community on the Sea Islands off of South Carolina – former West African slaves who adopted many of their ancestors’ Yoruba traditions – struggle to maintain their cultural heritage and folklore while contemplating a migration to the mainland, even further from their roots. The first wide release by a black female filmmaker, DAUGHTERS OF THE DUST was met with wild critical acclaim and rapturous audience response when it initially opened in 1991. Casting a long legacy, DAUGHTERS OF THE DUST still resonates today, most recently as a major in influence on Beyonce’s video album Lemonade. Winner of the Cinematography Award and nominated for the Grand Jury Prize in the Dramatic competition at the Sundance Film Festival. Chosen for preservation by the National Film Preservation Board, USA
https://nhfpl.kanopy.com/node/4694913
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; cinéma; communication; cours; discipline; discours dominant; esclavagisme; fem3200; histoire et politique; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Les théories scientifiques ont-elles un sexe? : actes du colloque - Decerf, Anne (Éditions d'Acadie, 1991)
Keywords: amériques; approches et analyses; canada; cours; cycles supérieurs; discipline; fem9000; inégalités; régions géographiques; sciences; sexisme; systèmes d'oppressions

En mémoire de l’avenir : les stratégies de transformation dans la narration de Jovette Marchessault - Godard, Barbara (Voix et Images, 1991)
Keywords: amériques; approches et analyses; création littéraire; genre; québec; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; écriture des femmes*

La république des hommes: les Patriotes de 1837 face aux femmes - Greer, Allan (Revue d'histoire de l'Amérique française, 1991)
Cet article examine la dimension sexuelle de la Rébellion de 1837 dans le Bas-Canada et soutient que les femmes furent bien moins actives dans la lutte anti-gouvernementale qu'elles ne l'avaient été au XVIIIe siècle dans diverses émeutes et autres mouvements de résistance. L'explication de ce changement est liée au procès de « masculinisation » de la politique qui a lieu un peu partout en Occident à la même époque. Comme le républicain type de la première moitié du XIXe siècle, le patriote du Bas-Canada défend une conception essentiellement masculine de la citoyenneté en régime démocratique. D'autre part la conviction rousseauiste que la femme vertueuse doit se confiner dans son rôle domestique permet de comprendre les poussées occasionnelles de mysoginie contre les femmes qui affichent publiquement leur opposition au mouvement patriote.
Keywords: 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; his4550; histoire; histoire et politique; politique; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Sexe et genre. De la hiérarchie entre les sexes - Hurtig, Marie-Claude (CNRS, 1991)
S’inscrivant dans le mouvement des études féministes qui ont marqué les années quatre-vingt, cet ouvrage réunit les différents points de vue de femmes universitaires engagées dans des champs de recherches aussi divers que la biologie, le droit, la linguistique. Partant de l’examen critique de la distinction sexe et genre, elles analysent les mécanismes qui assurent le maintien de la domination masculine et font progresser la réflexion sur les déterminants de la subordination des femmes.
http://catalogue.bnf.fr/ark:/12148/cb355381311
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; approches et analyses; cours; discriminations; europe; fem1000; france; genre; identités LGBTQIA2+; interdisciplinarité; inégalités; postmodernisme; premier cycle; psy4910; périodes historiques; rapports sociaux de sexe; régions géographiques; sexe/genre; systèmes d'oppressions; thématiques

A lure of knowledge: Lesbian sexuality and theory - Roof, Judith (Columbia University Press, 1991)
Lesbianism in literature has been dealt with rather indirectly in the past. Editors have led readers to the "artistry" of a work containing lesbianism, emphasizing instead the literary history and historical context of the work rather than the representations of lesbianism. The editor for Colette's The Pure and the Impure, for instance, affirms that Colette has a knowledge of a "strange sisterhood," but assures readers she has never strayed from the "normal." In the groundbreaking A Lure of Knowledge, Judith Roof demonstrates that representations of lesbian sexuality occupy specific locations or positions in the arguments, subject matter, and rhetoric of Western European and American literary criticism. She examines the political context of representations: how lesbian sexuality is used as a signifier an why it appears when and where it does. Roof argues that attempts to depict or explain lesbian sexuality spur anxieties about knowledge and identity. In reaction to and denial of these anxieties, lesbian sexuality is represented in film, literature, theory, and criticism as foreplay, as simulated heterosexuality, as erotic excess, as joking inauthenticity, as artful compromise, or as masculine mask in a specific repertoire of neutralization and evasion. Challenging the heterosexism of film theory and feminist theory, this book analyzes the rhetorical use of lesbian sexuality. Roof explores a range of discourses, from the woks of such authors as Anais Nin, Olga Broumas, Julia Kristeva, Jane Rule, Luce Iriguray, and Sigmund Freud, to films such as Emmanuelle, Desert Hearts, Entre Nous, and I've Heard the Mermaids Singing, to professional tennis.
Keywords: approches et analyses; arts; cinéma; communication; discipline; hétérosexisme; lesbianisme; personnes lesbiennes; sexualité; sexualité lesbienne; systèmes d'oppressions; thématiques; études culturelles; études littéraires

De la mère patriarcale à la mère légendaire : Triptyque lesbien de Jovette Marchessault - Saint-Martin, Lori (Voix et Images, 1991)
Keywords: amériques; approches et analyses; arts; discipline; histoire et politique; maternité; patriarcat; personnes lesbiennes; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; études littéraires